Modern views of brainstem and spinal cord leukoencephalopathy with increased lactate content - A. Yu. Ryabchenko; A. E. Gubina (Кубанский научный медицинский вестник)
The review considers modern evidence on a rare genetic disease, leukoencephalopathy of brainstem and spinal cord associated with elevated lactate content. The research history of the disease is described. The epidemiology of the disease prevalence in a population is described. Emphasis is placed on aetiology of leukoencephalopathy and peculiar genetic and pathomorphological changes associated with a DARS2 gene mutation leading to mitochondrial aspartyl-tRNA synthetase deﬁciency. The review details the clinical picture, manifestations speciﬁc in various age groups and identiﬁes diseases with similar clinical symptoms and morbid changes that require differential diagnosis. Modern relevant diagnostic approaches are outlined based primarily on neuroimaging techniques. The major neuroimaging approach to leukoencephalopathy is magnetic resonance imaging that allows detection of disease-speciﬁc lesion patterns in the brainstem and spinal cord. Magnetic resonance spectrometry is used in turn to detect a usually higher lactate content in the affected white matter of the brain. Deﬁnitive diagnosis is based on detection of the marker DARS2 mutation in patients with characteristic clinical picture and MRI signatures in the brain and spinal cord. The review describes contemporary treatment strategies utilising pathogenetic effects to potentially contain the disease. However, its genetic determination renders symptomatic therapy yet a common treatment.